The Effect of Using Different Types of Ginger on the Quality of Dadak Beef Randang - Adlim, Rino Fitra; Elida, Elida; Fridayati, Lucy; Zulfikar, Dikki (Jurnal Pendidikan Tata Boga dan Teknologi, 2024)
This research aims to analyze the effect of using different types of ginger on the quality of meat rendang, based on the differences in the types of ginger and the chemical composition contained in red ginger, emprit ginger and elephant ginger. And people tend to use ground ginger so that the type and quality of ginger that has been finely ground is not known. The aim of this research is to examine differences in the quality of randang meat in terms of shape, color, aroma, texture and taste. This type of research is a pure experiment with the aim of revealing the influence and differences between three different variables. The research design used was a completely randomized design (CRD). Data was obtained from 3 expert panelists, using an organoleptic test format, then the data was analyzed using a variance analysis test. If the ANOVA results show that Fcount is greater than Ftable, then the Duncan test is carried out. The results of the study revealed that there was no significant effect on the use of different types of ginger on the quality of the meat rendang, including the quality of the shape, color, aroma, texture and taste of the randang. From this statement, it can be concluded that H0 is accepted, namely the type of ginger does not affect the quality of the dadak randang because Fcount < Ftable.